Determinism of the symmetry of a single-crystalline surface of interface at obtaining 0D- and 2D-structues of noble metals and indium on silicon - Karbivska, L.I.; Karbivskyy, V.L.; Romanskyy, A.O. (Успехи физики металлов, 2019)
The review article deals with ‘quantum engineering’ of growing of silver films on semiconductor substrates that allows obtaining new forms of matter. The results on the energy dispersion of electron states in epitaxial Ag (111) films obtained on Si (001) and Si (111) are presented. Оглядову статтю присвячено «квантовій інженерії» вирощування плівок срібла на напівпровідникових підкладинках, яке уможливлює одержання нових форм речовини. Наведено результати з енергетичної дисперсії електронних станів у епітаксіальних плівках Ag (111), одержаних на Si (001) та Si (111). Обзорная статья посвящена «квантовой инженерии» выращивания пл нок серебра на полупроводниковых подложках, которое позволяет получать новые формы вещества. Приведены результаты по энергетической дисперсии электронных состояний в эпитаксиальных пл нках Ag (111), полученных на Si (001) и Si (111).